Copper paste for forming sintered copper pillars and method for producing joint body
The use of a copper paste with high boiling point solvents stabilizes sintered copper pillar formation, addressing time and consistency issues in existing methods, resulting in improved joining strength and reduced signal reflection.
Patent Information
- Application Number
- JP2021548891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-25
- Filing Date
- 2020-09-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Existing methods for forming copper pillars in electronic devices face challenges such as time-consuming processes and variations in pillar height, leading to inconsistent joining and potential signal reflection due to impedance issues at heterogeneous metal interfaces.
A copper paste containing copper particles and an organic dispersion medium with high boiling point solvents is used to form sintered copper pillars, allowing for stable joining even after prolonged precursor formation, with a composition that includes 50-99% high boiling point solvent by mass, facilitating efficient and accurate pillar formation.
The method enables stable formation of sintered copper pillars with improved joining strength and reduced signal reflection, enhancing connection reliability and conductivity while reducing process time from pillar precursor formation to mounting.
Smart Images

Figure 0007622634000004 
Figure 0007622634000005 
Figure 0007622634000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper paste for forming a sintered copper pillar and a method for producing a bonded body. [Background technology]
[0002] Solder joints are generally used for electrical joints in electronic devices. For example, in flip-chip joints of microdevices, solder balls or solder paste are used to join the microdevice to electrode pads on a substrate.
[0003] In recent years, in flip-chip bonding, as the pitch of terminals becomes narrower, a method has been used in which metal pillars are formed on microdevices and the metal pillars are soldered to electrode pads on a substrate. However, solder bonding has problems such as (1) Kirkendall voids occurring between the solder and the electrode pads and between the solder and the metal pillars, (2) when a reflow process is performed again after bonding, the solder melts and causes bonding failure, and (3) signal reflection occurs due to impedance mismatch at the interface between different metals.
[0004] In response to this, methods of bonding using metals other than solder are being considered. For example, the following Patent Document 1 proposes a method of bonding between a copper pillar provided on a microdevice and a copper pad on a substrate using a bonding agent (copper paste) containing a mixture of copper microparticles and copper nanoparticles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] US Patent Application Publication No. 2016 / 0351529 Summary of the Invention [Problem to be solved by the invention]
[0006] The method of Patent Document 1 requires the formation of copper pillars on the device in advance, but the mainstream copper pillar formation method, electrolytic plating, has the problem that it takes time to form the pillars. Another problem is that increasing the plating speed results in large variations in height.
[0007] Therefore, the present inventors have been studying a method of forming a sintered copper pillar and bonding the bonding members together by forming a pillar precursor between bonding members using a copper paste containing copper particles and an organic dispersion medium and sintering the pillar precursor. This method makes it possible to form a sintered copper pillar efficiently and accurately. However, as a result of the present inventors' studies, it has become clear that when it takes a long time (for example, about 1 to 3 hours) from the formation of the pillar precursor to the mounting of the bonding member, the bonding between the pillar and the bonding member may be insufficient.
[0008] The present invention has been made in consideration of the above circumstances, and aims to provide a copper paste for forming a sintered copper pillar that can stably form a joint body joined with a sintered copper pillar, even when the pillar precursor is left to stand for a long time and then a joining member is mounted and sintered, and a method for manufacturing a joint body using the copper paste. [Means for solving the problem]
[0009] One aspect of the present invention provides a copper paste for forming a sintered copper pillar that joins components together, the copper paste containing metal particles and an organic dispersion medium, the metal particles containing copper particles, and the organic dispersion medium containing 50 to 99 mass% of a high-boiling point solvent having a boiling point of 280°C or higher, based on the total mass of the organic dispersion medium.
[0010] According to the copper paste of the above aspect, even when the pillar precursor is left for a long time (e.g., about 1 to 3 hours) and then a joining member is mounted and sintered, a joined body joined with a sintered copper pillar can be stably formed.
[0011] The content of the high boiling point solvent is preferably 5 to 30 mass % based on the total mass of the copper paste.
[0012] The organic dispersion medium may contain two or more high boiling point solvents.
[0013] The copper paste preferably contains, as a high boiling point solvent, at least one selected from the group consisting of isobornylcyclohexanol and butyl stearate.
[0014] Another aspect of the present invention provides a method for producing a bonded body comprising a first member, a second member, and a sintered copper pillar joining the first member and the second member, the method comprising the steps of forming the copper paste of the side surface into a pillar shape on the first member, mounting the second member, and providing a pillar precursor between the first member and the second member, and forming a sintered copper pillar by sintering the pillar precursor.
[0015] According to the manufacturing method of the bonded body described above, a time leeway of about 1 to 3 hours can be provided from the formation of the pillar precursor to the mounting of the bonding members, so that the bonded body can be manufactured simply and stably. Effect of the Invention
[0016] According to the present invention, it is an object of the present invention to provide a copper paste for forming a sintered copper pillar that can stably form a joint body joined with a sintered copper pillar even when a pillar precursor is left to stand for a long time before mounting and sintering a joining member, and a method for manufacturing a joint body using the copper paste. [Brief description of the drawings]
[0017] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a bonded body according to the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating one embodiment of a method for producing a bonded body according to the present invention. [Diagram 3]1 is a schematic cross-sectional view illustrating one embodiment of a method for producing a bonded body according to the present invention. [Figure 4] 1 is a schematic cross-sectional view illustrating one embodiment of a method for producing a bonded body according to the present invention. [Diagram 5] 1 is a schematic cross-sectional view showing one embodiment of a joining pillar member according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified or considered to be obviously essential in principle. The same applies to the numerical values and their ranges, and they do not limit the present invention.
[0019] In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the purpose of the process is achieved. In this specification, a numerical range indicated using "to" indicates a range including the numerical values before and after "to" as the minimum and maximum values, respectively. In this specification, the content of each component in a composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, "boiling point" means the boiling point at 1 atmosphere.
[0020] <zygote> Fig. 1 is a schematic cross-sectional view for explaining one embodiment of a bonded body according to the present invention. The bonded body 10 shown in Fig. 1 includes a first member 1, a second member 2, and a sintered copper pillar 3 that bonds the first member 1 and the second member 2 together.
[0021] The lower and upper surfaces of the sintered copper pillar form the bonding surfaces with the first and second members, respectively, and the two are bonded together by metallic bonding. The formation of such metallic bonding allows the bonded body to have low electrical resistance and be firmly bonded.
[0022] Examples of the first member 1 and the second member 2 include an active or passive electronic device, a wiring board on which an electronic device is mounted, and a package having an electronic device and a rewiring layer provided on the electronic device.
[0023] Examples of electronic devices include coils, capacitors, SAW filters, power ICs, logic chips, memory chips, sensors, piezoelectric elements, transistors, and diodes.
[0024] Examples of wiring boards include mounting substrates, lead frames such as copper lead frames, ceramic substrates, resin molded products having printed metal wiring such as MIDs (Molded Interconnect Devices), and packages having rewiring layers.
[0025] One of the first and second members may be an active or passive electronic device, and the other may be a wiring board on which the electronic device is mounted, thereby enabling highly reliable mounting of the electronic device.
[0026] Furthermore, both the first member and the second member may be a package having an electronic device and a redistribution layer provided on the electronic device, which enables highly reliable package-on-package mounting.
[0027] The first member and / or the second member may have one or more metals selected from the group consisting of copper, nickel, silver, platinum, gold and palladium on the bonding surface with the sintered copper pillar. These metals can reduce and remove the oxide film on the surface at a sintering temperature of 300°C or less in a reducing atmosphere such as hydrogen or formic acid. Therefore, the bonded body can have high bonding strength due to the metallic bond between the exposed metal surface of the member and the sintered copper pillar. The above metals may be provided as a metal film or a sintered metal layer on the first member and / or the second member.
[0028] The copper content in the sintered copper pillar is preferably 96% by mass or more, more preferably 96.5% by mass or more, and even more preferably 97% by mass or more, based on the total mass of the components constituting the sintered copper pillar (excluding carbon, oxygen, and nitrogen). Note that the above carbon, oxygen, and nitrogen are components that may be unintentionally contained in the sintered copper pillar due to filling of an underfill or a sealing material during mounting.
[0029] When the copper content in the sintered copper pillar is within the above range, it is easy to form the sintered copper pillar by printing and sintering the copper paste for forming the sintered copper pillar described later, and it is advantageous in terms of ensuring the bonding strength and suppressing electromigration. In addition, when the bonding surface contains copper, the bonding is performed by the same metal, so it is easy to suppress the occurrence of Kirkendall voids, and a bonded body with even better connection reliability can be obtained.
[0030] From the viewpoint of thermal conductivity and electrical conductivity, the volume ratio of copper in the sintered copper pillar is preferably 50 volume % or more, more preferably 60 volume % or more, and even more preferably 70 volume % or more. The larger the volume ratio of copper in the sintered copper pillar, the higher the thermal conductivity and electrical conductivity of the sintered copper pillar, which is preferable. In this specification, the parts of the sintered copper pillar other than copper are expressed as pores. However, when a resin component such as a filler or underfill is contained in the pores, the volume of the component is also included in the volume of the pores. The volume ratio of copper in the sintered copper pillar can be obtained from an SEM image of the cross section of the sintered copper pillar.
[0031] The shortest distance H between the bonding surface with the first component and the bonding surface with the second component of the sintered copper pillar (sometimes referred to as the "height of the sintered copper pillar") may be 5 to 200 μm, 10 to 150 μm, or 20 to 100 μm.
[0032] The minimum diameter W of the sintered copper pillar in a cross section perpendicular to the extension direction of the pillar (sometimes referred to as the "width (diameter) of the sintered copper pillar") may be 10 to 500 μm, 25 to 300 μm, or 50 to 150 μm.
[0033] The ratio (H / W) of the above H to the above W in the sintered copper pillar (sometimes referred to as the "cross-sectional aspect ratio of the sintered copper pillar") may be 0.01 to 4.0, 0.1 to 2.5, or 0.15 to 2.0.
[0034] The above H and W can be determined from an SEM image of a cross section of the sintered copper pillar.
[0035] In the bonded body of this embodiment, the shear strength between the bonding surface of the first member and / or the second member and the sintered copper pillar can be 4 MPa or more, may be 10 MPa or more, or may be 20 MPa or more. In this case, the bonding surface of the first member and / or the second member can have the above-mentioned metal, and may have the above-mentioned metal as a metal layer.
[0036] The shear strength can be calculated, for example, by using a bonding strength testing device to push the sintered copper pillar horizontally at a constant speed with the tool of the device, and dividing the maximum strength at which the bonding surface between the sintered copper pillar and the component peels off by the cross-sectional area of the pillar.
[0037] <Method of manufacturing the bonded body> The method for producing the bonded body of the present embodiment is a method for producing the bonded body of the present embodiment described above, and includes a step of forming a sintered copper pillar by sintering a pillar precursor disposed between a first member and a second member. The pillar precursor contains metal particles and an organic dispersion medium, and the metal particles can contain copper particles.
[0038] In this embodiment, a copper paste (copper paste for forming sintered copper pillars) is formed into a pillar shape on a first component, for example by printing, and then a second component is mounted on the first component, thereby providing a pillar precursor between the first component and the second component.
[0039] [Copper paste for forming sintered copper pillars] The copper paste for forming a sintered copper pillar according to this embodiment contains metal particles and an organic dispersion medium, and the metal particles include copper particles.
[0040] Examples of copper particles include submicro copper particles and micro copper particles. Submicro copper particles refer to copper particles having a particle size of 0.01 μm or more and less than 0.8 μm. Micro copper particles refer to copper particles having a particle size of 0.8 μm or more and 50 μm or less.
[0041] The copper paste of the present embodiment preferably contains sub-micro copper particles from the viewpoint of easily ensuring the bonding strength and connection reliability. The copper paste may further contain micro copper particles and / or other metal particles other than copper particles as necessary.
[0042] (Submicron copper particles) As the submicro copper particles, copper particles having sinterability in a temperature range of 150°C to 300°C can be used. As the submicro copper particles, copper particles having a particle size of 0.01 μm to less than 0.8 μm can be used. For example, copper particles having a volume average particle size of 0.01 μm to less than 0.8 μm can be used. If the volume average particle size of the submicro copper particles is 0.01 μm or more, effects such as reduction in the synthesis cost of the submicro copper particles, good dispersibility, and reduction in the amount of surface treatment agent used can be easily obtained. If the volume average particle size of the submicro copper particles is less than 0.8 μm, the effect of excellent sinterability of the submicro copper particles can be easily obtained. From the viewpoint of further achieving the above effect, the upper limit of the volume average particle size of the submicro copper particles may be 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. In addition, the lower limit of the volume average particle size of the submicro copper particles may be 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more. The volume average particle size of the sub-micro copper particles may be, for example, 0.01 μm or more and 0.5 μm or less, 0.12 μm or more and less than 0.8 μm, 0.15 μm or more and less than 0.8 μm, 0.15 μm or more and 0.6 μm or less, 0.2 μm or more and 0.5 μm or less, or 0.3 μm or more and 0.45 μm or less.
[0043] In this specification, the volume average particle size means a 50% volume average particle size. When determining the volume average particle size of copper particles, the copper particles as raw material or dried copper particles obtained by removing volatile components from copper paste are dispersed in a dispersion medium using a dispersant, and the volume average particle size can be determined by a method such as measuring with a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (SALD-7500nano, manufactured by Shimadzu Corporation)). When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, 4-methyl-1,3-dioxolan-2-one, etc. can be used as the dispersion medium.
[0044] The shape of the sub-micro copper particles is not particularly limited. The sub-micro copper particles may be, for example, spherical, blocky, needle-like, columnar, flake-like or approximately spherical, or may be an aggregate of particles of these shapes. From the viewpoint of dispersibility and packing property, the shape of the sub-micro copper particles may be spherical, approximately spherical or flake-like, and from the viewpoint of combustibility, dispersibility, mixability with flake-like microparticles, etc., it may be spherical or approximately spherical. In this specification, "flake-like" includes flat plate-like shapes such as plate-like and scale-like.
[0045] The aspect ratio of the sub-micro copper particles may be 5 or less, 4 or less, or 3 or less, from the viewpoints of dispersibility, packing property, and mixability with the flake-shaped microparticles. In this specification, the "aspect ratio of a particle" (e.g., the aspect ratio of a sub-micro copper particle) refers to the long side / thickness of a particle (e.g., a sub-micro copper particle). The long side and thickness of a particle can be measured, for example, from an SEM image of the particle.
[0046] The submicron copper particles may be treated with a specific surface treatment agent, such as an organic acid having 2 to 18 carbon atoms (e.g., an organic acid having an alkyl group having 1 to 17 carbon atoms).Examples of organic acids having 2 to 18 carbon atoms include acetic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, caprylic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, pelargonic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, capric acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnon ... , butyl octanoic acid, pentyl heptanoic acid, tridecanoic acid, methyl dodecanoic acid, ethyl undecanoic acid, propyl decanoic acid, butyl nonanoic acid, pentyl octanoic acid, myristic acid, methyl tridecanoic acid, ethyl dodecanoic acid, propyl undecanoic acid, butyl decanoic acid, pentyl nonanoic acid, hexyl octanoic acid, pentadecanoic acid, methyl tetradecanoic acid, ethyl tridecanoic acid, propyl dodecanoic acid, butyl undecanoic acid, pentyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid, proline saturated fatty acids such as propyltridecanoic acid, butyldodecanoic acid, pentylundecanoic acid, hexyldecanoic acid, heptylnonanoic acid, heptadecanoic acid, octadecanoic acid, methylcyclohexanecarboxylic acid, ethylcyclohexanecarboxylic acid, propylcyclohexanecarboxylic acid, butylcyclohexanecarboxylic acid, pentylcyclohexanecarboxylic acid, hexylcyclohexanecarboxylic acid, heptylcyclohexanecarboxylic acid, octylcyclohexanecarboxylic acid, and nonylcyclohexanecarboxylic acid; octenoic acid, nonenoic acid, methylnonanoic acid, unsaturated fatty acids such as decenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, sapienic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, and linolenic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, and nonylbenzoic acid. The organic acid may be used alone or in combination of two or more.By combining such an organic acid with the sub-micron copper particles, it tends to be possible to achieve both the dispersibility of the sub-micron copper particles and the desorption property of the organic acid during sintering.
[0047] The amount of the surface treatment agent may be from 0.07% by mass to 2.1% by mass, from 0.10% by mass to 1.6% by mass, or from 0.2% by mass to 1.1% by mass.
[0048] Submicro copper particles can be commercially available. Commercially available submicro copper particles include, for example, CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.36 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.72 μm), Tn-Cu100 (manufactured by Taiyo Nippon Sanso Co., Ltd., volume average particle diameter 0.12 μm) and Cu-C-40 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle diameter 0.2 μm).
[0049] The content of the submicro copper particles may be 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more, based on the total mass of the metal particles, and may be 100% by mass or less, 95% by mass or less, 90% by mass or less, or 80% by mass or less. The content of the submicro copper particles may be 30% by mass or more and 100% by mass or less, 40% by mass or more and 90% by mass or less, 50% by mass or more and 95% by mass or less, 50% by mass or more and 80% by mass or less, 60% by mass or more and 80% by mass or less, or 60% by mass or more and 90% by mass or less, based on the total mass of the metal particles. If the content of the submicro copper particles is within the above range, it is easy to ensure the bonding strength of the bonded body obtained by sintering the pillar precursor formed by the copper paste, and when the member of the bonded body is a microdevice, the microdevice tends to exhibit good die shear strength and connection reliability.
[0050] The content of the submicro copper particles may be 20% by mass or more and 95% by mass or less, 30% by mass or more and 85% by mass or less, or 40% by mass or more and 75% by mass or less, based on the total amount of the copper paste, from the viewpoints of promoting sintering, achieving good connection between the first and second components, and exhibiting low-temperature sintering properties.
[0051] (Micro copper particles) As the micro copper particles, copper particles having a particle size of 0.8 μm or more and 50 μm or less can be used, for example, copper particles having a volume average particle size of 0.8 μm or more and 50 μm or less can be used.
[0052] It is preferable to mix micro copper particles in combination with submicro copper particles. In this case, volume shrinkage and void generation when sintering the pillar precursor formed by the copper paste can be reduced, and it is easy to ensure the bonding strength of the bonded body obtained by sintering the pillar precursor, and when the member of the bonded body is a micro device, the micro device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the volume average particle size of the micro copper particles may be 0.8 μm or more and 20 μm or less, 0.8 μm or more and 10 μm or less, 2 μm or more and 20 μm or less, 2 μm or more and 10 μm or less, 3 μm or more and 20 μm or less, or 3 μm or more and 10 μm or less.
[0053] The shape of the micro copper particles is not particularly limited. The micro copper particles may be, for example, spherical, lump-like, needle-like, flake-like or approximately spherical, or may be an aggregate of particles of these shapes.
[0054] In this embodiment, flake-shaped micro copper particles can be combined with sub-micro copper particles. In this case, the micro copper particles in the pillar precursor are oriented approximately parallel to the bonding surface, so that the volume shrinkage in the bonding surface direction when the pillar precursor is sintered can be suppressed, and the bonding strength of the bonded body obtained by sintering the pillar precursor can be easily ensured. When the member of the bonded body is a micro device, the micro device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the aspect ratio of the flake-shaped micro copper particles is preferably 3 or more, more preferably 4 or more, and even more preferably 6 or more.
[0055] In the micro copper particles, the presence or absence of treatment with a surface treatment agent is not particularly limited. From the viewpoint of dispersion stability and oxidation resistance, the micro copper particles may be treated with a surface treatment agent. The surface treatment agent may be one that is removed during bonding. Examples of such surface treatment agents include aliphatic carboxylic acids such as dodecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, arachidic acid, linoleic acid, linoleic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornylcyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanenitrile; silane coupling agents such as alkylalkoxysilanes; and polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. The surface treatment agent may be used alone or in combination of two or more.
[0056] The micro copper particles can be commercially available. Examples of commercially available flake-shaped micro copper particles include MA-C025KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 7.5 μm), 4L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3.0 μm), 3L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 5.7 μm), 3L3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 8.0 μm), 2L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle diameter 9.9 μm), 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 3.8 μm), 1050YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.94 μm), 1100YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 1.2 μm), 1200YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 3.4 μm), and 1400YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 5.2 μm).
[0057] Examples of spherical or nearly spherical micro copper particles include 1050Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 0.81 μm), 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.1 μm), 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 2.1 μm), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.6 μm), 1400Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 5.5 μm), 1200YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.9 μm), 1300YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.4 μm), 1400YM (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.2 μm), Cu-HWQ Examples of such Cu-HWQ powders include Cu-HWQ 1.5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 1.5 μm), Cu-HWQ 1.5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 1.4 μm), Cu-HWQ 3.0 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3.0 μm), Cu-HWQ 5.0 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 4.1 μm), and Cu-HWQ 10 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 9.4 μm).
[0058] The content of the micro copper particles may be 0% by mass or more, more than 0% by mass, 5% by mass or more, or 10% by mass or more, and may be 70% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the metal particles. The content of the micro copper particles is preferably 0% by mass or more and 70% by mass or less, more preferably 0% by mass or more and 70% by mass or less, even more preferably 5% by mass or more and 50% by mass or less, and particularly preferably 10% by mass or more and 40% by mass or less, based on the total mass of the metal particles.
[0059] The copper paste of the present embodiment may contain micro copper particles having a volume average particle size of 0.8 μm to 50 μm, preferably micro copper particles having a volume average particle size of 2 μm to 50 μm, at a ratio of more than 0 mass% to 50 mass% based on the total mass of the metal particles. In this case, volume shrinkage and void generation during sintering of the pillar-shaped copper paste can be reduced, and the bonding strength of the bonded body bonded by the sintered copper pillar can be easily ensured.
[0060] When flake-shaped micro copper particles are blended, from the viewpoint of effectively obtaining the above-mentioned effects, the content of the flake-shaped micro copper particles is preferably 0% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and even more preferably 10% by mass or more and 40% by mass or less, based on the total mass of the metal particles. From the viewpoint of suppressing the variation in the height of the pillar precursor while sufficiently ensuring the strength of the sintered copper pillar and further suppressing the occurrence of cracks, the content of the flake-shaped micro copper particles is particularly preferably 20% by mass or more and 40% by mass or less.
[0061] The copper paste of this embodiment may contain copper nanoparticles to the extent that the effects of the microcopper particles and submicrocopper particles described above are not impaired. Copper nanoparticles refer to copper particles having a particle size of less than 0.01 μm. From the viewpoint of making the sintered copper pillars denser and increasing the copper content, the content of copper nanoparticles is preferably 30% by mass or less, more preferably 15% by mass or less, even more preferably 5% by mass or less, particularly preferably 1% by mass or less, based on the total mass of the metal particles, and is extremely preferably 0% by mass, i.e., does not contain copper nanoparticles.
[0062] (Metal particles other than copper particles) The metal particles may contain other metal particles other than copper particles, such as submicro copper particles and micro copper particles, and may contain, for example, zinc, nickel, silver, gold, palladium, platinum, etc. The volume average particle size of the other metal particles other than copper particles may be 0.01 μm or more and 10 μm or less, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less. When the metal particles contain other metal particles, the content thereof may be less than 20 mass%, 10 mass% or less, 5 mass% or less, or 1 mass% or less based on the total mass of the metal particles from the viewpoint of obtaining sufficient bonding properties. The metal particles may not contain other metal particles. The shape of the other metal particles is not particularly limited.
[0063] The content of the other metal particles may be 1% by mass or more, or 5% by mass or more, based on the total mass of the metal particles. When the copper paste contains metal particles other than copper particles, particularly when it contains metal particles having a metal species with a low melting point, the sintering temperature can be lowered. Furthermore, since a sintered body in which multiple types of metals are dissolved or dispersed can be obtained, the mechanical properties of the sintered body, such as the yield stress and fatigue strength, are improved, and the connection reliability is likely to be improved. Furthermore, by adding multiple types of metal particles, the sintered body can have sufficient bonding strength with respect to a specific adherend. When the member of the bonded body is a microdevice, the die shear strength and connection reliability of the microdevice are likely to be improved.
[0064] (Organic dispersion medium) The organic dispersion medium includes a solvent having a boiling point of less than 280°C (hereinafter also referred to as a "low boiling point solvent") and a solvent having a boiling point of 280°C or more (hereinafter also referred to as a "high boiling point solvent"). In this embodiment, the content of the high boiling point solvent is 50 to 99 mass% based on the total mass of the organic dispersion medium. By using such an organic dispersion medium, it is possible to stably form a bonded body bonded with a sintered copper pillar even when the pillar precursor is left for a long time and then a bonding member is mounted and sintered. The reason why such an effect is obtained is not clear, but the inventors presume that the type and amount of the organic dispersion medium in the pillar precursor affect the formation of a stable sintered copper pillar. That is, in the present invention, the amount of the high boiling point solvent contained in the pillar precursor is unlikely to change between the formation of the pillar precursor and the mounting of the bonding member, and the adhesion and flexibility are maintained by a certain amount of the high boiling point solvent remaining in the pillar precursor, and as a result, it is considered that the above effect is obtained. In addition, the low boiling point solvent provides appropriate fluidity, making it easy to mold the copper paste into pillar shapes.
[0065] As the low boiling point solvent, from the viewpoint of forming pillars more efficiently and with higher accuracy, a solvent having a boiling point of 270° C. or less is preferable, a solvent having a boiling point of 260° C. or less is more preferable, and a solvent having a boiling point of 250° C. or less is even more preferable. The boiling point of the low boiling point solvent is, for example, 200° C. or more.
[0066] Examples of low boiling point solvents include α-terpineol, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, 4-methyl-1,3-dioxolan-2-one, and dihydroterpineol. The low boiling point solvent can be easily removed in the drying process or temperature increase process before sintering the pillar precursor. Among these, α-terpineol and dihydroterpineol are preferred because they can form pillars more efficiently and with higher accuracy when combined with a high boiling point solvent described later. The low boiling point solvent may be used alone or in combination with multiple types.
[0067] As the high boiling point solvent, a solvent having a boiling point of 290°C or more is preferred, and a solvent having a boiling point of 300°C or more is more preferred. A dispersion medium having such a boiling point is likely to remain in the pillar precursor up to the firing temperature of 150°C to 300°C, so that adhesion and flexibility are more likely to be maintained. In addition, by using a dispersion medium having such a boiling point, there is a tendency that the standing time (the time from the formation of the pillar precursor to the mounting of the joining member) during which stable formation of the joining by the sintered copper pillar is possible can be made longer. On the other hand, as a solvent having a boiling point of 280°C or more, a solvent having a boiling point of 450°C or less is preferred, and a solvent having a boiling point of 400°C or less is more preferred. The solvent is volatilized and removed by its vapor pressure even at a temperature below its boiling point, but a solvent having a boiling point of more than 450°C is likely to cause sintering inhibition due to the remaining solvent, because the volatilization speed is too slow even at the sintering temperature of 150°C to 300°C.
[0068] As the high-boiling point solvent, it is preferable to select a solvent having a structure with high affinity to the surface of metal particles in order to improve the dispersibility of the contained metal particles (e.g., copper particles such as submicro copper particles and micro copper particles). For example, when the metal particles are surface-treated with a surface treatment agent containing an alkyl group, it is preferable to select a solvent having an alkyl group. As a combination of the surface treatment agent of the metal particles and the high-boiling point solvent, it is preferable that the surface treatment agent is an organic acid containing an alkyl group having 1 to 17 carbon atoms, and the high-boiling point solvent is a solvent containing an alkyl group having 1 to 17 carbon atoms, it is more preferable that the surface treatment agent is an organic acid containing an alkyl group having 5 to 17 carbon atoms, and the high-boiling point solvent is a solvent containing an alkyl group having 5 to 17 carbon atoms, and it is even more preferable that the surface treatment agent is an organic acid containing an alkyl group having 10 to 17 carbon atoms, and the high-boiling point solvent is a solvent containing an alkyl group having 10 to 17 carbon atoms. According to the above combination, the metal particles can be dispersed well even when the content of the high-boiling point solvent is increased.
[0069] Specific examples of high-boiling point solvents include isobornylcyclohexanol (MTPH, manufactured by Nippon Terpene Co., Ltd.), butyl stearate, Exepar BS (manufactured by Kao Corporation), stearyl stearate, Exepar SS (manufactured by Kao Corporation), 2-ethylhexyl stearate, Exepar EH-S (manufactured by Kao Corporation), isotridecyl stearate, Exepar TD-S (manufactured by Kao Corporation), isooctadecanol, Fine Oxocol 180 (manufactured by Nissan Chemical Industries, Ltd.), Fine Oxocol 180T (manufactured by Nissan Chemical Industries, Ltd.), 2-hexyldecanol, Fine Oxocol 1600 (manufactured by Nissan Chemical Industries, Ltd.), tributyrin, tetraethylene glycol, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, and methylheptadecanol. Examples of the isocyanate include butyl ether, tridecyl cyclohexane, tetradecyl cyclohexane, pentadecyl cyclohexane, hexadecyl cyclohexane, undecyl benzene, dodecyl benzene, tetradecyl benzene, tridecyl benzene, pentadecyl benzene, hexadecyl benzene, heptadecyl benzene, nonyl naphthalene, diphenylpropane, octyl octanoate, methyl myristate, ethyl myristate, methyl linoleate, methyl stearate, triethylene glycol bis(2-ethylhexanoic acid), tributyl citrate, pentylphenol, dibutyl sebacate, oleyl alcohol, cetyl alcohol, methoxyphenethyl alcohol, benzyl phenol, hexadecane nitrile, heptadecyl nitrile, benzyl benzoate, and cinmethylin. Among these, isobornylcyclohexanol, isotridecyl stearate, octyl octanoate, 2-ethylhexyl stearate, and butyl stearate are preferred, isobornylcyclohexanol, octyl octanoate, and butyl stearate are particularly preferred, and isobornylcyclohexanol and butyl stearate are further preferred. The high boiling point solvent may be used alone or in combination of two or more kinds.When two or more high-boiling point solvents are used in combination, the solvent with high viscosity is diluted by the other solvent, and the viscosity of the paste is reduced, and the paste's plate-release property and coating performance are improved, compared to when, for example, a relatively high-boiling point solvent (isobornylcyclohexanol, butyl stearate, etc.) is used alone. In addition, when butyl stearate (freezing point of about 25°C) is used as one of the two or more high-boiling point solvents, the freezing point is lowered, and the paste tends to be prevented from solidifying. In particular, isobornylcyclohexanol is preferably used in combination with tributyrin. In addition, butyl stearate is preferably used in combination with octyl octanoate.
[0070] The content of the high boiling point solvent is 50% by mass or more based on the total mass of the organic dispersion medium, and is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, from the viewpoint of preventing volatilization from the pillar precursor and allowing it to remain in the pillar precursor until sintering. The content of the high boiling point solvent is 99% by mass or less based on the total mass of the organic dispersion medium, and is preferably 98% by mass or less, more preferably 97.5% by mass or less, from the viewpoint of facilitating accurate molding of the copper paste into a pillar shape by printing.
[0071] When isobornylcyclohexanol is used as the high boiling point solvent, the content of isobornylcyclohexanol may be 10 mass% or more, 15 mass% or more, or 30 mass% or more, and 50 mass% or less, 45 mass% or less, or 30 mass% or less, based on the total mass of the organic dispersion medium. The content of isobornylcyclohexanol may be 10 to 50 mass%, 15 to 45 mass%, or 20 to 30 mass%, based on the total mass of the organic dispersion medium.
[0072] When butyl stearate is used as the high boiling point solvent, the content of butyl stearate may be 20% by mass or more, 30% by mass or more, or 40% by mass or more based on the mass of the organic dispersion medium from the viewpoint of improving the dispersibility of copper particles and from the viewpoint of easily remaining in the pillar precursor until sintering. The content of butyl stearate may be 70% by mass or less, 60% by mass or less, or 55% by mass or less based on the mass of the organic dispersion medium from the viewpoint of facilitating accurate molding of the copper paste into a pillar shape by printing. From these viewpoints, the content of butyl stearate may be 20 to 70% by mass, 30 to 60% by mass, or 40 to 55% by mass based on the mass of the organic dispersion medium.
[0073] The content of the high boiling point solvent is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 8% by mass or more, based on the total mass of the copper paste. In this case, the amount of the high boiling point solvent in the pillar precursor tends to be sufficient, and stable pillar formation tends to be facilitated. The content of the high boiling point solvent is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on the total mass of the copper paste. In this case, it tends to be easy to form the copper paste into a pillar shape with high accuracy by printing. From these viewpoints, the content of the high boiling point solvent is preferably 5 to 30% by mass, more preferably 7 to 25% by mass, and even more preferably 8 to 20% by mass, based on the total mass of the copper paste.
[0074] The content of the organic dispersion medium may be 5 to 50 parts by mass relative to 100 parts by mass of the metal particles. If the content of the organic dispersion medium is within the above range, the viscosity of the copper paste can be adjusted to a more appropriate value, and the sintering of the copper particles is not easily inhibited.
[0075] The type of organic dispersion medium contained in the copper paste can be analyzed, for example, by gas chromatography-mass spectrometry of high-temperature desorbed gas and TOF-SIMS. Other analytical methods include a method in which the supernatant obtained by separating particle components by centrifugation is identified by conventional organic analysis (for example, FT-IR, NMR, liquid chromatography, and combinations thereof). The ratio of types of organic dispersion medium can be quantified by liquid chromatography, NMR, etc.
[0076] (Flexibility imparting component) The copper paste of the present embodiment may contain a flexibility-imparting component, such as a thermally decomposable resin.
[0077] The thermally decomposable resin is preferably a non-crystalline polymer capable of exhibiting adhesiveness or tackiness from the viewpoint of temporarily fixing the adherend and the pillar precursor from after the pillar precursor is formed until the pillar precursor is fired. In addition, the thermally decomposable resin preferably has thermal decomposition properties that allow it to decompose at the sintering temperature without leaving any residue.
[0078] The thermal decomposition temperature of the thermally decomposable resin is preferably 300° C. or lower, and more preferably 250° C. or lower. The thermal decomposition temperature of the thermally decomposable resin is the decomposition initiation temperature of the thermally decomposable resin, which is the temperature at which the resin starts to lose 5% weight in TG / DTA measurement. However, this temperature does not mean the decomposition initiation temperature in an oxidizing atmosphere such as air, but in a reducing atmosphere containing hydrogen, formic acid, etc., or in an inert gas atmosphere from which oxygen has been removed.
[0079] The less the residue after pyrolysis of the pyrolyzable resin, the better since it hinders the sintering of the copper particles. The amount of residue after pyrolysis of the pyrolyzable resin is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less, based on the total mass of the resin before pyrolysis. The amount of residue after pyrolysis of the pyrolyzable resin can be measured as the weight change amount after holding at the sintering temperature for the sintering time by TG / DTA of the pyrolyzable resin in an inert gas (nitrogen or argon) containing 3 to 5% by mass of hydrogen. Note that TG / DTA measurement in air is not preferred because the amount of residue is less than that in a reducing atmosphere due to the progress of oxidative decomposition.
[0080] The thermally decomposable resin preferably has solubility in the organic dispersion medium. Examples of thermally decomposable resins having solubility in the organic dispersion medium and the desired properties include polycarbonate, polymethacrylic acid, polymethacrylic acid ester, and polyester.
[0081] The content of the thermally decomposable resin in the copper paste may be 25% by mass or less, 15% by mass or less, 5% by mass or less, or 3% by mass or less based on the total mass of the copper paste. If the purpose is to form a sintered copper pillar, the thermally decomposable resin does not need to be blended. On the other hand, from the viewpoint of increasing the proportion of the flexibility-imparting component contained in the total solvent and reducing the progress of drying, the content of the thermally decomposable resin in the copper paste may be 5% by mass or more based on the total mass of the copper paste.
[0082] The copper paste for forming sintered copper pillars of this embodiment can be adjusted to a viscosity suitable for a printing / coating method for forming a pillar precursor. The viscosity of the copper paste at 25°C may be 50 Pa·s or more and 2000 Pa·s or less, 100 Pa·s or more and 1750 Pa·s or less, or 200 Pa·s or more and 1500 Pa·s or less. When the viscosity of the copper paste is within the above range, it becomes easy to form a pillar precursor by various printing methods described later.
[0083] In this specification, the viscosity of the copper paste for forming sintered copper pillars means a value measured by an E-type viscometer at 25° C. and a rotation speed of 0.5 rpm. As the E-type viscometer, for example, a viscometer manufactured by Toki Sangyo Co., Ltd. under the trade name: VISCOMETER-TV33 type viscometer can be used. As a measuring tool for a cone rotor, for example, 3°×R14, SPP can be used.
[0084] The thixotropy index (hereinafter also referred to as TI value) of the copper paste for forming a sintered copper pillar of this embodiment may be 2.0 or more and 20 or less, 3.0 or more and 15 or less, or 4.0 or more and 10 or less. If the TI value of the copper paste is within this range, the viscosity of the copper paste is reduced by shear force, so that it becomes easier to print by stirring it manually or with a stirring device (for example, a rotation-revolution type stirring device (Planetary Vacuum Mixer ARV-310, manufactured by Thinky Corporation) before printing, and after the copper paste is attached to the member to be adhered, the viscosity is restored by leaving it to stand, which makes it possible to suppress excessive wetting and spreading of the printed matter.
[0085] In this specification, the TI value is the viscosity measured using an E-type viscometer at 25°C and a rotation speed of 0.5 rpm. 0.5 When the viscosity measured at 25°C and a rotation speed of 5 rpm is μ5, the value was calculated using the following formula. TI value = μ 0.5 / μ5
[0086] [Preparation method of copper paste] The copper paste can be prepared by mixing the above-mentioned copper particles, an organic dispersion medium, and, if necessary, a flexibility-imparting component, other metal particles, and any additives. For example, the flexibility-imparting component can be prepared by dissolving it in an organic solvent, and then adding submicro copper particles, micro copper particles, other metal particles, and any additives to perform a dispersion treatment. Alternatively, the copper paste can be prepared by mixing a solution in which the flexibility-imparting component is mixed and dissolved in an organic solvent, a dispersion in which copper particles are mixed in a solvent and dispersed, and other metal particles and any additives. In addition, when the dispersibility of the high-boiling point solvent and the metal particles is not sufficient, the copper paste may be prepared by dispersing the metal particles in a low-boiling point solvent and then adding and mixing a high-boiling point solvent. When the combination of the surface treatment agent for the metal particles and the high-boiling point solvent is the above-mentioned preferred combination, such an operation is not necessary, so that a metal paste containing a larger amount of the high-boiling point solvent can be prepared more efficiently.
[0087] When the copper particles include submicro copper particles and micro copper particles, a dispersant may be added to the organic solvent or the flexibility imparting component as necessary, and the submicro copper particles may be mixed and dispersed, and then the micro copper particles and, if necessary, other metal particles may be added and dispersed. The dispersion method and dispersion conditions suitable for the dispersion of submicro copper particles and micro copper particles may differ. In general, submicro copper particles require a stronger dispersion than micro copper particles, while micro copper particles are easily dispersed and a low dispersion strength is sufficient, and micro copper particles may be deformed by strong dispersion. By following the above procedure, the dispersibility is improved, and the performance of the copper paste can be further improved. The dispersion may be classified to remove aggregates.
[0088] In this preparation method, a stirring process may be performed after mixing the components. The maximum particle size of the dispersion of the copper paste may be adjusted by a classification operation. In this case, the maximum particle size of the dispersion can be 20 μm or less, or 10 μm or less.
[0089] The dispersion treatment can be carried out using a dispersing machine or agitating machine, examples of which include an Ishikawa type agitating machine, a Silverson agitating machine, a cavitation agitating machine, a rotation-revolution type agitating machine, an ultra-thin film high-speed rotary dispersing machine, an ultrasonic dispersing machine, a Raikai machine, a twin-screw kneading machine, a bead mill, a ball mill, a triple roll mill, a homomixer, a planetary mixer, an ultra-high pressure type dispersing machine, and a thin layer shear dispersing machine.
[0090] The stirring treatment can be carried out using a stirrer, such as an Ishikawa stirrer, a rotation-revolution type stirrer, a Raikai mixer, a twin-screw kneader, a three-roll mill, or a planetary mixer.
[0091] The classification operation can be carried out, for example, by filtration, natural sedimentation, centrifugation, etc. Examples of filters for filtration include water combs, metal meshes, metal filters, nylon meshes, etc.
[0092] [Formation of pillar precursors] In the method of this embodiment, a copper paste (copper paste for forming sintered copper pillars) is printed onto a first component to form a pillar shape, and then a second component is mounted on the first component to provide a pillar precursor between the first component and the second component.
[0093] Examples of a printing method for the copper paste that can be used include screen printing, transfer printing, offset printing, jet printing, a dispenser, a jet dispenser, a needle dispenser, a comma coater, a slit coater, a die coater, a gravure coater, a slit coat, letterpress printing, intaglio printing, gravure printing, stencil printing, soft lithography, a bar coat, an applicator, a particle deposition method, a spray coater, a spin coater, a dip coater, and electrochemical coating.
[0094] From the viewpoints of simple manufacturing process, easy maintenance of shape stability, and easy thick-film printing, it is preferable to form the copper paste into a pillar shape by screen printing or stencil printing. In this case, for example, a metal mask 4 is placed on the first member 1 (FIG. 2(a)), and then a copper paste 3a is spread using a squeegee 5 to fill the holes in the metal mask 4 with the copper paste 3a (FIGS. 2(b) and 2(c)). In this way, the copper paste 3b formed into a pillar shape is provided on the first member 1 (FIG. 3(a)).
[0095] The metal mask used for screen printing or stencil printing may have a via diameter of 30 μm to 200 μm, or 50 μm to 100 μm. The holes may be arranged in a lattice shape with a pitch of 1 μm to 500 μm. The squeegee angle may be 10° to 90°, or 45° to 70°.
[0096] The printing height H1 may be 5 μm or more and 500 μm or less, or 10 μm or more and 200 μm or less. In addition, the wetting spread W1 from the pillar end after printing may be 100 μm or less, or 50 μm or less.
[0097] The indentation depth (H1-H2) when the second component 2 is mounted may be 500 μm or less, 100 μm or less, or 50 μm or less from the top of the pillar-shaped copper paste. H2 is set in consideration of the height of the sintered copper pillar or pillar precursor to be formed.
[0098] When the first and second members are, for example, a microdevice and a substrate, the second member can be mounted using, for example, a chip mounter, a flip chip bonder, or a positioning jig made of carbon or ceramics.
[0099] In this way, a pillar precursor 3c is provided between the first member 1 and the second member 2 (FIG. 3(b)).
[0100] Next, the pillar precursor 3c disposed between the first member 1 and the second member 2 is sintered to form a sintered copper pillar 3, thereby obtaining a bonded body 10 (FIG. 3(c)).
[0101] The pillar precursor may be appropriately dried from the viewpoint of suppressing flow and generation of voids during sintering. The gas atmosphere during drying may be air, an oxygen-free atmosphere such as nitrogen or a rare gas, or a reducing atmosphere such as hydrogen or formic acid. The drying method may be drying by leaving at room temperature, drying by heating, or drying under reduced pressure. For example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate pressing device, etc. can be used for drying by heating or drying under reduced pressure. The temperature and time of drying may be appropriately adjusted according to the type and amount of the organic dispersion medium and the flexibility-imparting component used. The temperature and time of drying may be, for example, 50°C or higher and 180°C or lower for 30 seconds to 120 minutes.
[0102] The pillar precursor can be sintered by heat treatment, for example, using a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, or the like.
[0103] The gas atmosphere during sintering may be a reducing atmosphere from the viewpoint of removing the copper particles contained in the pillar precursor and the surface oxide of the deposition surface. Examples of the reducing atmosphere include pure hydrogen gas, a mixed gas of hydrogen and nitrogen such as forming gas, nitrogen containing formic acid gas, a mixed gas of hydrogen and a rare gas, and a rare gas containing formic acid gas.
[0104] In this embodiment, when the diameter of the pillar precursor is small (especially when it is 200 μm or less), the formic acid penetrates into the inside of the pillar precursor, making it easier to reduce the copper particles, and the copper particles can be sufficiently sintered in a reducing atmosphere containing formic acid gas. In this case, it is possible to sinter using a formic acid reflow furnace, and the degree of sintering can be efficiently improved.
[0105] The maximum temperature reached during the heat treatment may be 150° C. or higher and 300° C. or lower, 170° C. or higher and 250° C. or lower, or 200° C. or higher and 250° C. or lower, from the viewpoints of sufficiently advancing sintering, reducing thermal damage to members such as the microdevice and the substrate, and improving the yield. If the maximum temperature reached is 150° C. or higher, sintering tends to proceed sufficiently even if the maximum temperature is held for 60 minutes or less.
[0106] The time for which the maximum temperature is maintained may be from 1 minute to 60 minutes, from the viewpoint of being able to sufficiently remove the organic dispersion medium and the flexibility-imparting component, to sufficiently advance sintering, and to improve the yield, or may be from 1 minute to less than 40 minutes, or may be from 1 minute to less than 30 minutes.
[0107] The method for manufacturing the bonded body of the present embodiment may further include a step of filling the periphery of the sintered copper pillar with resin, in which case a bonded body 20 is obtained in which a sealing material 6 is provided between the first member 1 and the second member 2 (FIG. 4).
[0108] As the sealing material, from the viewpoint of protecting the joining portion from heat, moisture and impact and further improving the connection reliability, a compression molding sealing material, a liquid sealing material, a transfer molding sealing material, an underfill sealing material, etc. can be used.
[0109] <Parts with connecting pillars> The joining pillar-equipped component of this embodiment is, for example, a joining pillar-equipped component that comprises a component having a metal layer and a pillar provided on the metal layer, and is joined to another component via the pillar, in which the pillar is made of sintered copper, the copper content of the pillar is 96 mass% or more based on the total mass of the components constituting the pillar (excluding carbon, oxygen, and nitrogen), and the volume ratio of copper in the pillar is 50 volume% or more.
[0110] Fig. 5 is a schematic cross-sectional view showing one embodiment of a joining member with pillars. The joining member with pillars 30 shown in Fig. 5 includes a first member 1 and a pillar 3d provided on the first member 1. The joining member with pillars 30 is joined to a second member.
[0111] The joining pillar-equipped member 30 can be obtained, for example, in the same manner as in the manufacturing method of the joined body of the present embodiment described above, by forming copper paste into a pillar shape on a first member (Figure 3 (a)) and then sintering the copper paste formed into a pillar shape.
[0112] Selection of members, preparation of copper paste, molding of copper paste, and sintering can be performed in the same manner as in the manufacturing method of the bonded body of the present embodiment described above. The same also applies to the preferred conditions.
[0113] The joining pillar made of sintered copper and having the above-mentioned configuration can be formed in a shorter time than electrolytic plating, has excellent thermal conductivity and electrical conductivity, and is less susceptible to electromigration. A joining pillar-equipped member having such a pillar can easily ensure the connection reliability of a joined body obtained by joining to another member, and can shorten the manufacturing process of the joined body.
[0114] When the joining pillar-equipped member of this embodiment is joined to another member via a pillar, a copper paste can be used. In this case, the pillar is joined with the same type of sintered copper, so that the electromigration resistance is improved, Kirkendall voids are suppressed, the thermal conductivity is improved, and the data transmission characteristics are improved, resulting in a package with excellent connection reliability and electrical characteristics. The above copper paste can be configured in the same manner as the copper paste for forming the sintered copper pillar of this embodiment. EXAMPLES
[0115] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0116] Example 1 The copper paste was prepared, a bonded body was produced and evaluated, and a bonding member with pillars was produced and evaluated by the following methods.
[0117] [Preparation of copper paste] 0.058 g of α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.), 0.256 g of tributyrin (dispersion medium), and a slurry mixture (CH-200: α-terpineol = 91: 9, mass ratio) of previously prepared CH-0200 (submicro copper particles, product name of Mitsui Kinzoku Co., Ltd., 50% volume average particle size: 0.36 μm, surface treatment agent: lauric acid) and α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.) 2.189 g, 0.493 g of 3L3N (flake-shaped micro copper particles, product name of Fukuda Metal Foil Powder Co., Ltd., volume average particle size: 5.7 μm), and 0.006 g of zinc (other metal particles, manufactured by Alfa Aesar, product number: 13789) were kneaded in an agate mortar until the dry powder disappeared, and the mixed liquid was transferred to a poly bottle.
[0118] The sealed plastic bottles were mixed in a planetary vacuum mixer (ARV-310, manufactured by Thinky Corporation) for 2000 min. -1 The mixture was stirred at 2000 rpm for 2 minutes to obtain copper paste 1.
[0119] [Preparation of junction] A bonded body was formed by the following method using copper paste 1. A stainless steel metal mask (784 openings per 7 mm, thickness: 50 μm) with φ130 μm openings arranged in a grid pattern with a pitch of 250 μm was placed on a copper plate (15 mm square, thickness 0.3 mm) as a first member, and the copper paste was applied by stencil printing using a metal squeegee. After the copper paste was applied, it was left at room temperature for a predetermined time, and a Ni-plated Si chip (3 mm square, thickness 0.15 mm) as a second member was placed on the pillar-shaped copper paste on the substrate, and pressed 10 μm from the top of the Si chip using a spacer-equipped pressing tool. The predetermined time was 1 hour, 2 hours, and 3 hours. Then, these laminates (copper plate / pillar precursor / Si chip) were placed in a hydrogen sintering furnace (100% hydrogen reducing atmosphere), heated to 225 ° C at a heating rate of 7.5 ° C / min, and held at 225 ° C for 60 minutes. Thereafter, the resulting mixture was cooled to 200°C over 5 minutes, held at 200°C for 5 minutes, and then rapidly cooled to room temperature to obtain bonded body 1 (which had a Si chip mounted after being left for 1 hour), bonded body 2 (which had a Si chip mounted after being left for 2 hours), and bonded body 3 (which had a Si chip mounted after being left for 3 hours).
[0120] [Evaluation of bonding condition 1] The bonded bodies 1 to 3 were turned over and subjected to a slight vibration to perform a simple evaluation of the bondability, and the bonded state was evaluated according to the following criteria. The results are shown in Table 1. [Judgment criteria] A: None of the Si chips in the bonded bodies 1 to 3 peeled off and remained on the copper substrate. B: The Si chips of the bonded bodies 1 and 2 did not peel off, but the Si chip of the bonded body 3 peeled off. C: The Si chip of the bonded body 1 did not peel off, but the Si chips of the bonded bodies 2 and 3 peeled off. D: All of the Si chips in the bonded bodies 1 to 3 peeled off.
[0121] [Evaluation of bonding condition 2] The bonded body obtained in the above Evaluation 1 was placed in a cup and fixed with a sample clip (Samplklip I, manufactured by Buehler). An epoxy casting resin (product name "Epomount", manufactured by Refine Tech Co., Ltd.) was poured around the bonded body until the entire bonded body was buried in the resin. The bonded body was then placed in a vacuum desiccator and degassed by reducing the pressure for 1 minute.
[0122] The sample was then left at room temperature (25°C) for 10 hours to harden the epoxy casting resin, and a casting sample was obtained. The casting sample was cut near the cross section to be observed using a Refine Saw Excel (Refine Tech) with a resinoid cutting wheel. The cross section was then polished using a polishing device (Refine Polisher HV, Refine Tech) with waterproof abrasive paper (Carbomac Paper, Refine Tech) to expose the joints of the sintered copper pillars. Furthermore, the end protruding from the mask was polished using an ion milling device "IM4000" (Hitachi) in CP mode, and a sample for observation was prepared.
[0123] The cross section of the bonded portion of the observation sample was observed at various magnifications with an applied voltage of 15 kV. In the bonded portion where the Si chip was not peeled off, it was confirmed that the sintered copper pillar was metallically bonded to the adherend.
[0124] (Examples 2 and 3) Copper pastes 2 and 3 were obtained in the same manner as in Example 1, except that the amounts of each component were adjusted so that the contents of each component were values shown in Table 1. A bonded body was produced and evaluated in the same manner as in Example 1, except that the obtained copper paste 2 or 3 was used. The results are shown in Table 1.
[0125] (Examples 4 and 5) Copper pastes 4 and 5 were obtained in the same manner as in Example 1, except that isobornylcyclohexanol (Tersorb MTPH, manufactured by Nippon Terpene Chemical Co., Ltd.) was used as the dispersion medium, and the amount of each component was adjusted so that the content of each component was the value shown in Table 1. A bonded body was produced and evaluated in the same manner as in Example 1, except that the obtained copper paste 4 or 5 was used. The results are shown in Table 1.
[0126] Example 6 0.1772 g of octyl octanoate (dispersion medium, manufactured by Sigma-Aldrich Japan Co., Ltd.), 2.0308 g of a slurry mixture (CH-200: α-terpineol: butyl stearate = 91: 0.9: 8.1, mass ratio) of CH-0200 (submicro copper particles, product name of Mitsui Kinzoku Co., Ltd., 50% volume average particle size: 0.36 μm), α-terpineol (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.) and butyl stearate (dispersion medium, manufactured by Wako Pure Chemical Industries, Ltd.), 0.7867 g of 3L3N (flake-shaped micro copper particles, product name of Fukuda Metal Foil Powder Co., Ltd., volume average particle size: 5.7 μm), and 0.006 g of zinc (other metal particles, manufactured by Alfa Aesar, product number: 13789) were kneaded in an agate mortar until the dry powder disappeared, and the mixed liquid was transferred to a poly bottle.
[0127] The sealed plastic bottles were mixed in a planetary vacuum mixer (ARV-310, manufactured by Thinky Corporation) for 2000 min. -1 (2000 rpm) for 2 minutes. Thus, copper paste 6 was obtained. A bonded body was produced and evaluated in the same manner as in Example 1, except that the obtained copper paste 6 was used. The results are shown in Table 1.
[0128] (Examples 7 to 11) Copper pastes 7 to 11 were obtained in the same manner as in Example 6, except that the blending amounts of each component were adjusted so that the content of each component was the value shown in Table 2. Bonded bodies were produced and evaluated in the same manner as in Example 1, except that the obtained copper pastes 7 to 11 were used, respectively. The results are shown in Table 2.
[0129] (Comparative Examples 1 to 3) Copper pastes 12 to 14 were obtained in the same manner as in Example 1, except that the blending amounts of each component were adjusted so that the content of each component was the value shown in Table 3. Note that the α-terpineol used in Comparative Example 2 was only the α-terpineol contained in the slurry mixture, and no α-terpineol was added during kneading. Except that the obtained copper pastes 12 to 14 were used, respectively, bonded bodies were produced and evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3] [Explanation of symbols]
[0133] 1...first member, 2...second member, 3...sintered copper pillar, 3a...copper paste, 4...metal mask, 5...squeegee, 10, 20...joint, 30...member with joining pillar.
Claims
1. A copper paste for forming a sintered copper pillar that bonds components together, Contains metal particles and an organic dispersion medium, the metal particles include copper particles, The organic dispersion medium contains 50 to 99 mass% of a high-boiling point solvent having a boiling point of 280° C. or more, based on the total mass of the organic dispersion medium.
2. The copper paste according to claim 1, wherein the content of the high boiling point solvent is 5 to 30 mass% based on the total mass of the copper paste.
3. The copper paste according to claim 1 or 2, wherein the organic dispersion medium contains two or more of the high boiling point solvents.
4. The copper paste according to any one of claims 1 to 3, wherein the high boiling point solvent comprises at least one selected from the group consisting of isobornylcyclohexanol and butyl stearate.
5. A method for manufacturing a joined body including a first member, a second member, and a sintered copper pillar joining the first member and the second member, comprising the steps of: A step of forming the copper paste according to any one of claims 1 to 4 into a pillar shape on the first member, mounting the second member, and providing a pillar precursor between the first member and the second member; and forming the sintered copper pillar by sintering the pillar precursor.
Citation Information
Patent Citations
Composite wiring board and manufacturing method thereof
JP2003110240A
Pillar forming past, manufacturing method of pillar, manufacturing method of bump structure, pillar and bump structure
JP2016115846A
Method for electrical coupling and electric coupling arrangement
US20160351529A1
Method for producing joined body, and joining material
WO2019093427A1